Bioremediation of canola cooking oil using cold-adapted Antarctic bacterial community from soils - Mohd Zahri, Khadijah Nabilah (2023)
Hydrocarbons can cause pollution to Antarctic terrestrial and aquatic ecosystems, both through accidental release and the discharge of waste cooking oil in greywater. Such pollutants can persist for long periods in cold environments. In this study, using mixed native Antarctic bacterial communities, several environmental factors influencing biodegradation of waste canola oil (WCO) and canola oil (CO) were optimised using established one-factor-at-a-time (OFAT) and response surface methodology (RSM) approaches. Secondary mathematical equations were chosen for kinetic analyses and the effect of co-contaminant heavy metals on WCO biodegradation was discussed. The toxicity of different heavy metals in 1 ppm of concentration to the WCO-degrading bacteria was evaluated and further analysed using half-maximal inhibition concentration (IC50) and effective concentration (EC50) tests. Next, biosurfactant production was optimised using RSM after preliminary screening processes. The bacterial community was then investigated through metagenomics analysis and so with lipase-producing bacteria was identified using Sanger sequencing. As for the result, an Antarctic soil bacterial community (reference BS14) was confirmed to biodegrade canola oil. Using OFAT, the most effective microbial community examined was able to degrade 94.42% and 86.83% (from an initial concentration of 0.5% (v/v)) of WCO and CO, respectively, within 7 days. Using RSM, 94.99% and 79.77% degradation of WCO and CO was achieved in 6 days. Mathematical modelling demonstrated that the best-fitting model was the Haldane model for both WCO and CO degradation. Kinetic parameters including the maximum degradation rate (μmax) were obtained, which were 0.365 and 0.307 min−1 for WCO and CO degradation, respectively. As for heavy metal evaluation, the IC50 values of Ag and Hg for WCO degradation were 0.47 and 0.54 ppm, respectively. Meanwhile, Cr, As and Pb were well-tolerated and induced bacterial growth and WCO degradation, resulting in the EC50 values of 3.00, 23.80, and 28.98 ppm, respectively. Next, all preliminary screenings for biosurfactants were positive, where biosurfactant concentrations produced up to 13.44 and 14.06 mg/mL in the presence of WCO and CO, respectively, after optimisation. The bacterial community in non-treated media were originated from Proteobacteria and Firmicutes families. High proportions of bacterial families in WCO and CO treated media were Pseudomonadaceae (98.27%), followed by Carnobacteriaceae (1.70%). Among all the bacterial strains identified in the metagenomic analysis, it was confirmed that a group of Pseudomonas and Carnobacterium strains were responsible for biodegrading WCO and CO. Hence, this study offers a novel insight into the potential of the BS14 Antarctic bacterial community for canola oil bioremediation in Antarctica due to its ability to degrade WCO and CO effectively and produce biosurfactant at the same time. Plus, the BS14 community was able to tolerate heavy metals while biodegrading WCO in low-temperature conditions, which is a crucial aspect in biodegrading oil due to the co-contamination of oil and heavy metals that can occur simultaneously, and at the same time it can be applied in heavy metal-contaminated areas.